2018
DOI: 10.1155/2018/9746438
|View full text |Cite
|
Sign up to set email alerts
|

Model Test Research on Bearing Mechanism of Underreamed Ground Anchor in Sand

Abstract: To improve the capacity of ground anchors, scholars and engineers worldwide have developed various types of underreamed anchors with expanded anchor parts. Underreamed anchors have a completely different mechanism from traditional shaft anchors. The expanded section of an underreamed anchor induces an end bearing force to endure the uplift force similar to a reversed pile. Therefore, the total resistance of an underreamed anchor includes friction and end bearing force. To clarify the bearing mechanism of under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Compared with a single enlarged anchor, a multibell underreamed anchor can significantly improve the uplift capacity 10 , and the influence of burial depth cannot be ignored 11 . Scholars have studied the position of the enlarged body on the anchor 12 , the enlargement shape 13 and the underreamed size 14 , 15 , but these factors have not been comprehensively considered.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a single enlarged anchor, a multibell underreamed anchor can significantly improve the uplift capacity 10 , and the influence of burial depth cannot be ignored 11 . Scholars have studied the position of the enlarged body on the anchor 12 , the enlargement shape 13 and the underreamed size 14 , 15 , but these factors have not been comprehensively considered.…”
Section: Introductionmentioning
confidence: 99%
“…Although the increase of the bladder space shows a positive effect on improving the ultimate pulling force and controlling the anchor deformation, such improvement is less efficient. erefore, it can be inferred that there may be an effective space, and it will produce a reverse effect when exceeding the space [47], which can be explained with that the working area of the bladder is limited, and the effect will be reduced once the bladder space is beyond the area. 6 Advances in Civil Engineering 3.5.…”
Section: Bladder Spacementioning
confidence: 99%
“…Under grout injection, they can seamlessly expand and grout, ensuring continuous support. Guo Gang et al [8] using FBI sensors, monitored the frictional forces and end forces experienced by the hole-expanding anchor rod during pullout. Their findings revealed that the anchor rod's load-bearing capacity primarily stems from the end forces in the expanding section, and this capacity positively correlates with burial depth.…”
Section: Introductionmentioning
confidence: 99%